2016
DOI: 10.1063/1.4942093
|View full text |Cite
|
Sign up to set email alerts
|

Control of threshold voltage in E-mode and D-mode GaN-on-Si metal-insulator-semiconductor heterostructure field effect transistors by in-situ fluorine doping of atomic layer deposition Al2O3 gate dielectrics

Abstract: We report the modification and control of threshold voltage in enhancement and depletion mode AlGaN/GaN metal-insulator-semiconductor heterostructure field effect transistors through the use of in-situ fluorine doping of atomic layer deposition Al2O3. Uniform distribution of F ions throughout the oxide thickness are achievable, with a doping level of up to 5.5 × 1019 cm−3 as quantified by secondary ion mass spectrometry. This fluorine doping level reduces capacitive hysteretic effects when exploited in GaN met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Varieties of approaches, including gate recessed 2,3 , fluorine ion implantation 4 , p-GaN cap layer 5,6 have been exploited to achieve the normally-off behavior of GaN-based devices. The gate recessed approach is a promising technology since it enables to keep high mobility and high density of electrons without compromising the voltage threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of approaches, including gate recessed 2,3 , fluorine ion implantation 4 , p-GaN cap layer 5,6 have been exploited to achieve the normally-off behavior of GaN-based devices. The gate recessed approach is a promising technology since it enables to keep high mobility and high density of electrons without compromising the voltage threshold.…”
Section: Introductionmentioning
confidence: 99%
“…A 100 nm SiN x passivation layer was deposited by Plasma-Enhanced Chemical Vapor Deposition (PECVD), into which a 1.5 µm gate window was opened for F-implantation using a reactive ion etching process. In order to obtain E-mode operation, F-implantation was carried out in an inductively coupled plasma chamber with a 40 sccm (standard cubic centimeter per minute) CHF 3 34 ] for details). The structure was then annealed at 500 °C for 5 minutes under a nitrogen gas environment in a rapid thermal annealing chamber.…”
Section: Methodsmentioning
confidence: 99%
“…It is usually reported that the nitrogen vacant sites (V N ) act as the major source of free electrons and carrier traps , that may degrade the device properties over prolonged bias stress. To passivate such defects, researchers attempted fluorine plasma treatment or fluorine doping in nitride semiconductors. …”
Section: Introductionmentioning
confidence: 99%